Extracorporeal Membrane Oxygenation Use in Acute Myocardial Infarction in the United States, 2000 to 2014. (December 2019) - Vallabhajosyula, Saraschandra; Prasad, Abhiram; Bell, Malcolm R.; Sandhu, Gurpreet S.; Eleid, Mackram F.; Dunlay, Shannon M.; Schears, Gregory J.; Stulak, John M.; Singh, Mandeep; Gersh, Bernard J.; Jaffe, Allan S.; Holmes, David R.; et al.
Abstract : Background: Extracorporeal membrane oxygenation (ECMO) is increasingly used in acute myocardial infarction (AMI); however, there are limited large-scale national data. Methods: Using the National Inpatient Sample database from 2000 to 2014, a retrospective cohort of AMI utilizing ECMO was identified. Use of percutaneous coronary intervention, intra-aortic balloon pump, and percutaneous left ventricular assist device (LVAD) was also identified in this population. Outcomes of interest included temporal trends in utilization of ECMO alone and with concomitant procedures (percutaneous coronary intervention, intra-aortic balloon pump, and percutaneous LVAD), in-hospital mortality, and resource utilization. Results: In ≈9 million AMI admissions, ECMO was used in 2962 (<0.01%) and implanted a median of 1 day after admission. ECMO was used in 0.5% and 0.3% AMI admissions complicated by cardiogenic shock and cardiac arrest, respectively. ECMO was used more commonly in admissions that were younger, nonwhite, and with less comorbidity. ECMO use was 11× higher in 2014 as compared with 2000 (odds ratio, 11.37 [95% CI, 7.20–17.97]). Same-day percutaneous coronary intervention was performed in 23.1%; intra-aortic balloon pump/percutaneous LVAD was used in 57.9%, of which 30.3% were placed concomitantly. In-hospital mortality with ECMO was 59.2% overall but decreased from 100% (2000) to 45.1% (2014). Durable LVAD and cardiac transplantation were performed in 11.7% as an exit strategy. Of the hospital survivors, 40.8% were discharged to skilled nursing facilities. Older age, male sex, nonwhite race, and lower socioeconomic status were independently associated with higher in-hospital mortality with ECMO use. Conclusions: In AMI admissions, a steady increase was noted in the utilization of ECMO alone and with concomitant procedures (percutaneous coronary intervention, intra-aortic balloon pump, and percutaneous LVAD). In-hospital mortality remained high in AMI admissions treated with ECMO. Abstract : Supplemental Digital Content is available in the text.